Peningkatan motivasi belajar siswa melalui penggunaan aplikasi quizizz pada pembelajaran bahasa Indonesia di kelas V SD Negeri Golo Yogyakarta - Ningrum, Anggun Yuliana Sephia; Sudigdo, Anang (Universitas Sarjanawiyata Tamansiswa, 2025)
This class action research aims to describe the increase in student learning motivation through the use of quizizz applications in Indonesian language learning in class V SD Negeri Golo Yogyakarta. The hypothesis of this study is that through the use of quizizz applications can increase student learning motivation in learning Indonesian in grade V of SD Negeri Golo Yogyakarta. This research is a type of classroom action research conducted in two cycles with four stages, namely planning, implementation, observation and reflection. The research was conducted at SD Negeri Golo Yogyakarta with the research subjects being fifth grade students in the 2024/2025 school year totaling 23 students. The object of this research is to increase students learning motivation in learning Indonesian in grade V of SD Negeri Golo Yogyakarta. Data collection techniques in this study were questionnaires and tests. Data collection instruments in the form of student learning motivation questionnaire and learning outcomes test. The data analysis technique is in the form of questionnaire analysis to determine student learning motivation and tests to measure the learning outcomes of grade V students in Indonesian language subjects. The results showed that the use of the quizizz application proved effective in increasing student learning motivation. 1) The increase in the results of the student learning motivation questionnaire shows that the average percentage of learning motivation in the preaction was 40,51% in the low category. After using the quizizz application, the average percentage of learning motivation increased in cycle I by 78,74% in the good category and reached 84,87% in cycle II in the very good category with an increase of 6,13%. 2) The increase in student learning outcomes showed that the average student score in the initial condition was 70,17. After using the quizizz application, the average value increased to 79,39 in cycle I and reached 83,74 in cycle II. Thus, the use of the quizizz application in Indonesian language learning can increase student learning motivation in Class V of SD Negeri Golo Yogyakarta can be considered successful because it reaches the predetermined success indicators.